2010
DOI: 10.1152/ajpendo.00372.2010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic consumption of a high-fat/high-fructose diet renders the liver incapable of net hepatic glucose uptake

Abstract: Coate KC, Scott M, Farmer B, Moore MC, Smith M, Roop J, Neal DW, Williams P, Cherrington AD. Chronic consumption of a high-fat/ high-fructose diet renders the liver incapable of net hepatic glucose uptake. Am J Physiol Endocrinol Metab 299: E887-E898, 2010. First published September 7, 2010; doi:10.1152/ajpendo.00372.2010.-The objective of this study was to assess the response of a large animal model to high dietary fat and fructose (HFFD). Three different metabolic assessments were performed during 13 wk of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 39 publications
5
55
0
Order By: Relevance
“…In support of findings in animals [7,19,21,23,24] and humans [25,30,31], our data show that an HFD rapidly impairs the ability of insulin to suppress hepatic glucose output, with peripheral insulin resistance developing subsequently. Furthermore, our data suggest that the liver quantitatively has the most significant impact on postprandial glycaemia, as both peak glucose intolerance and hepatic insulin resistance occurred within 3-7 days of HFD, despite the absence of muscle insulin resistance at this time.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In support of findings in animals [7,19,21,23,24] and humans [25,30,31], our data show that an HFD rapidly impairs the ability of insulin to suppress hepatic glucose output, with peripheral insulin resistance developing subsequently. Furthermore, our data suggest that the liver quantitatively has the most significant impact on postprandial glycaemia, as both peak glucose intolerance and hepatic insulin resistance occurred within 3-7 days of HFD, despite the absence of muscle insulin resistance at this time.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, consistent with our hypothesis, we show that an increase in lipid metabolites are associated with defects in tissue insulin action, suggesting that lipotoxicity is a generalised mechanism associated with the induction of insulin resistance in individual tissues of mice. Studies in rodents [7,[19][20][21]23], dogs [24] and humans [25][26][27], have shown that short-term exposure to HFD/overfeeding (3-28 days) results in the rapid development of insulin resistance and glucose intolerance. Often these changes occur with only modest increases in fat mass, highlighting that metabolic defects occur prior to the onset of obesity and do not require extensive periods of fat feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of GCK gene expression by insulin may be modulated by dietary components such as dietary PUFA which decrease GCK gene expression induction (Jump et al 1994). Moreover, the long-term consumption of a diet high in fat and in fructose among dogs has shown to also decrease GCK protein and its activity in the liver as well as glycogen storage, but not mRNA abundance (Coate et al 2010(Coate et al , 2011Moore et al 2012). It has been observed that GCK mRNA abundance is positively correlated with the liver TG content (Peter et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Following each scanning session the animals were allowed to recover from the anesthesia. Details on the animal study design can be found in previously published work by Coate et al (7). Table positions for the thorax, chest, and abdomen were performed with breath-holding by temporarily deactivating the ventilator.…”
Section: Methodsmentioning
confidence: 99%
“…Though used often in human studies, whole-body FWMRI remains underutilized in large animal models such as dogs. The canine model is particularly valuable for obesogenic diet studies (7,8) that would be difficult to perform in a human cohort.…”
Section: Introductionmentioning
confidence: 99%